Mechanisms of Novel Host Use by Bactrocera tau (Tephritid: Diptera) Revealed by RNA Transcriptomes. Issue 5 (20th October 2020) - Shi, Wei; Roderick, George; Zhang, Gen-Song
Abstract: Use of novel plant hosts can facilitate the establishment and range expansion of herbivorous invasive species. However, the inherent mechanisms of novel host use are still unclear in many herbivorous species. Here, we examine mechanisms of novel host use in the invasive tephritid fruit fly Bactrocera tau (Walker)(Diptera: Tephritidae) by documenting changes in the RNA transcriptomes associated with a novel host. RNA transcripts of B. tau were obtained with high-throughput sequencing from samples continuously reared on two traditional Cucurbitaceae hosts and a novel host (banana). We found transcriptome variation was strongly associated with feeding on banana. Moreover, B. tau feeding on banana contained more differentially expressed genes (DEGs) and more annotated categories of DEGs in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database with 1, 595 DEGs and 21 major annotated pathways. The annotated categories of DEGs in individuals reared on banana differed with from those individuals feeding on other hosts and were enriched in oxidative phosphorylation, citrate cycle pathway, and four other carbohydrate pathways. For B. tau feeding on banana, the predominant numbers of upregulated genes in the mitochondrial NADH (56 on average) and a relatively higher numbers of upregulated genes (13 on average) were found in oxidative phosphorylation and the TCA pathway, respectively. Changes in RNA transcriptomes associated with novel host use, especially for genes related to energy and carbohydrate metabolism, help to explain how B. tau can be successful in use of novel hosts and may be useful in developing novel strategies for control of tephritid flies.